Sodium doping of solution‐processed amine‐thiol based CIGS solar cells by thermal evaporation of NaCl. (9th March 2021) - Uličná, Soňa; Welch, Liam M.; Abbas, Ali; Togay, Mustafa; Tsai, Vincent; Betts, Tom R.; Malkov, Andrei V.; Walls, John M.; Bowers, Jake W.
Abstract: Poor crystallinity, high degree of porosity and rough surfaces are the main drawbacks of solution‐processed CIGS absorbers resulting in lower power conversion efficiencies when compared to vacuum‐based CIGS solar cells. Therefore, promoting absorber grain growth is key to further improve solution‐based solar cell performance. The effect of alkali elements such as Na in CIGS absorbers is generally recognised to have beneficial effects not only on the absorber opto‐electronic properties but also on the grain growth. In this work, thermal evaporation of a thin layer of NaCl prior to selenisation resulted in absorbers with significantly larger CIGS grains than previously seen with Na diffusing directly from the from soda‐lime glass substrate. NaCl is non‐toxic, abundant and readily available compound that has not been typically used as an evaporation source, but rather as an additive into CIGS precursor solution. The effect of Na on these solution‐processed CIGS devices was primarily observed in the spectacular morphological changes leading to improved carrier collection and minority carrier lifetimes, but less on the absorber doping. Transmission electron microscopy (TEM) revealed voids forming around large CIGS grains upon NaCl addition and these had a negative effect on inter‐grain carrier transport. Nonetheless, the resulting device performance doubled from 5% to 10% with addition of Na using this doping approach; however, a compromise between the optimum grain growth and optimum electronic properties had to be made. This study demonstrates a novel, simple and effective Na‐doping strategy for CIGS absorbers and reveals the current limitations of the Na‐doping in solution‐processed atmospherically deposited cells. Abstract : Previously unexplored way of CIGS absorber doping by thermal evaporation of NaCl is presented. Solar cell performance doubled from 5% to 10% with deposition of 15–nm‐thick NaCl. Spectacular grain growth of solution‐processed CIGS absorbers with =30–nm NaCl was observed. The minority carrier lifetime increased with improved absorber morphology. Void formation and Ga segregation resulted in lower than expected photovoltaic (PV) performances.